Which Political Actors Frame the Immigration Problem? Documenting the Incidence of Source Type and Party Lines in Immigration Stories during U.S. Election Coverage (2006-2014). (9th August 2022) - Fernandes, Juliana; De Moya, Maria
ABSTRACT: This study investigates the framing of immigration by political actors in US election news from 2006 to 2014 and how they present the issue as a problem (for society, for immigrants, no problem frames). Through a content analysis of national newspapers coverage of midterm and presidential elections, we explore the relationship between the people sourced in the stories and the framing of immigration as a problem. Results show that despite an increasingly competitive framing field (with more non-governmental, non-elite sources salient in news coverage), government officials and candidates are still often mentioned in stories on immigration. Seen along party lines, framing of immigration as a problem for society is more associated with Republican government officials and candidates for office than with Democrats. Special interest groups and Law enforcement sources are also attached to immigration framing. Implications for the understanding of how the immigration issue is framed during electoral periods are discussed.